2023
DOI: 10.1111/1754-9485.13546
|View full text |Cite
|
Sign up to set email alerts
|

Delta‐radiomics‐based models for toxicity prediction in radiotherapy: A systematic review and meta‐analysis

Abstract: IntroductionDelta‐radiomics models are potentially able to improve the treatment assessment than single‐time point features. The purpose of this study is to systematically synthesize the performance of delta‐radiomics‐based models for radiotherapy (RT)‐induced toxicity.MethodsA literature search was performed following the PRISMA guidelines. Systematic searches were performed in PubMed, Scopus, Cochrane and Embase databases in October 2022. Retrospective and prospective studies on the delta‐radiomics model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 57 publications
(123 reference statements)
0
2
0
Order By: Relevance
“…Furthermore, it has been observed that the incidence of coronary events increases by 7.4 per 1 Gy increase in the mean heart dose [33]. In most studies, hybrid techniques (H-VMAT, H-IMRT) had lower heart doses than VMAT or IMRT [13][14][15][16][17][18]20], but some studies reported no statistically significant difference [25,27]. However, these latter studies included both breast and chest wall patients, which could affect the final result.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has been observed that the incidence of coronary events increases by 7.4 per 1 Gy increase in the mean heart dose [33]. In most studies, hybrid techniques (H-VMAT, H-IMRT) had lower heart doses than VMAT or IMRT [13][14][15][16][17][18]20], but some studies reported no statistically significant difference [25,27]. However, these latter studies included both breast and chest wall patients, which could affect the final result.…”
Section: Discussionmentioning
confidence: 99%
“…The search was conducted in the PubMed and Scopus databases using the population, intervention, control, and outcomes (PICO) framework to establish the search terms (Table 1, Appendix). This type of review is widely used to expand upon the current knowledge base to drive the development of healthcare practice [16][17][18]. Boolean search phrase combinations were used to guarantee that all pertinent articles were found (Supplementary A).…”
Section: Review Materials and Methodsmentioning
confidence: 99%